AN ACADEMIC APPROACH OF THE MILITARY DOCTRINE TRANSFORMATION IN THE CONTEXT OF ASYMMETRICAL CONFLICTS - GROSU, Ruslana (Strategic Impact, 2024)
Transformation of military doctrines in the context of asymmetric conflicts is an imperative to maintain the relevance and effectiveness of the military response to contemporary threats. This transformation requires a holistic approach that integrates technological innovations, international cooperation, interoperability, reflecting the dynamics and complexity of the global security environment. Military doctrine requires a foundation based on a thorough analysis of the existing threats and potential risks, provided that the asymmetric conflict imposes the need for a quick and adaptable reaction. Asymmetric conflicts differ from classic conflicts by involving a number of actors, and the integration of these actors in the planning and execution of military strategies can support post-conflict stabilization and reconstruction efforts, thus strengthening the resilience of communities and states facing asymmetric threats. Therefore, adapting military doctrines to the specifics of asymmetric conflicts is an ongoing process, which requires a flexible approach that allows military forces to respond effectively to a wide range of threats in a constantly changing security environment.